Democratic and Transformational Leadership of Susilo Bambang Yudhoyono in the Dynamics of Modern Indonesian Politics - Nurhasni Nurhasni; Hasnah Faizah AR (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This This article aims to conduct an in-depth analysis of Susilo Bambang Yudhoyono’s (SBY) leadership practices during his presidency (2004–2014), highlighting how his character, leadership style, policy implementation, and responses to the nation’s various challenges influenced the direction of Indonesia’s national development. The research employs a descriptive qualitative case study method by analyzing literature sources, government documents, state policies, and relevant academic studies. The findings show that SBY’s leadership was characterized by a democratic-participatory model with a charismatic touch, guiding Indonesia through critical periods such as major natural disasters, global economic changes, and challenges in consolidating democracy. The use of soft diplomacy, political consensus, and transparent governance became hallmarks of the SBY era, accompanied by bureaucratic reform efforts, social innovation, and community involvement in policy-making. This article also discusses the major achievements of SBY’s administration, responses to criticism, and the leadership legacy as a model for future national leaders.